Functional analysis of dry matter accumulation in pure artificial meadows - Maiorana M.; Stelluti M.; Ferri D. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
The aim of this paper is to assess the possibility of carrying out a functional analysis of dry matter accumulation in two forage crops, cocksfoot (Dactylis glomerata L.) and sainfoin (Onobrychis viciifolia Scop.), grown as dryland crop in Southern Italy. For each experimental factor examined (species, harvest time, cutting height), the Gompertz's logistical function at 3 parameters: W (t x ha -1) equals to a x exp (-exp (b-kt)) was adapted to determine the growth curves of dry matter over time. The function interpolated the data obtained extremely well. The following analysis of variance, univariate and multivariate, carried out on the values of the parameters of curves, allowed the discrimination of the growth trends.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)